2023
DOI: 10.3389/fpls.2023.1186376
|View full text |Cite
|
Sign up to set email alerts
|

Soil enzyme activities, soil physical properties, photosynthetic physical characteristics and water use of winter wheat after long-term straw mulch and organic fertilizer application

Abstract: IntroductionInappropriate residue and nutrient management leads to soil degradation and the decline of soil quality and water storage capacity.MethodsAn ongoing field experiment has been conducted since 2011 to investigate the effects of straw mulching (SM), and straw mulching combined with organic fertilizer (SM+O), on winter wheat yield, including a control treatment (CK, no straw). We studied the effects of these treatments on soil microbial biomass nitrogen and carbon, soil enzyme activity in 2019, photosy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 80 publications
0
12
0
Order By: Relevance
“…Reducing this mechanical damage prevents the infiltration capacity of the soil from gradually decreasing over time, and prevents deeper soil from drying out due to a lack of percolation. SS is thus beneficial for crop root growth, organic carbon content, and soil organism activity (Li et al, 2018) especially for the combination of subsoiling with organic fertilizer (Yang, Duan, et al, 2022;Yang, Li, et al, 2022; and straw mulching with organic fertilizer (Yang et al, 2023). In addition, compared to CS, SS improved soil pore circularity especially in the uppermost 50 cm of the soil (Figure 3), which allows moisture to be better retained and transported by the soil.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Reducing this mechanical damage prevents the infiltration capacity of the soil from gradually decreasing over time, and prevents deeper soil from drying out due to a lack of percolation. SS is thus beneficial for crop root growth, organic carbon content, and soil organism activity (Li et al, 2018) especially for the combination of subsoiling with organic fertilizer (Yang, Duan, et al, 2022;Yang, Li, et al, 2022; and straw mulching with organic fertilizer (Yang et al, 2023). In addition, compared to CS, SS improved soil pore circularity especially in the uppermost 50 cm of the soil (Figure 3), which allows moisture to be better retained and transported by the soil.…”
Section: Discussionmentioning
confidence: 99%
“…However, Schneider et al (2017) found that subsoiling could decrease crop yield due to nutrient leaching by high infiltration rates, which may result from differences in soil types. In addition, Yang, Duan, et al (2022), Yang, Li, et al (2022), and Yang et al (2023) found that subsoiling combined with organic fertilizer, and straw mulching coupled with organic fertilizer, both improved soil properties and soil organism activities, which led to increased crop yields. The effects on agricultural soil properties of straw mulching after long-term subsoiling tillage, or after long-term conventional tillage, have not been sufficiently researched.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wheat plant and soil enzymatic activity plays a critical role in determining the overall health and productivity of these essential agricultural components. It’s still unclear how these enzyme activities relate to the way they respond to drought stress [ 9 ]. To better understand how plants withstand dry conditions and develop strategies to mitigate the detrimental effects of water scarcity on agricultural output, we must gain insight into how drought stress affects these enzyme functions [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted by Zhou et al [15] revealed that straw mulching not only improved soil moisture retention and soil structure but also suppressed weed growth. According to a study written by Yang et al [16] the utilization of 4-6 t/ha of straw mulch has been found to significantly improve soil physical conditions in tropical regions. This includes the protection of the topsoil.…”
Section: Introductionmentioning
confidence: 99%